Using collaborative peer reflection to develop student teachers' practice - Nia Cole-Jones; Nerys Defis; Alison Glover; Mathew Jones; Rachel Wallis (Centre National d'Enseignement à Distance, 2024)
This paper reports on a project that supported the development of feedback, critical reflection and collaborative skills for student teachers using video technology. As a consequence of the Covid-19 restrictions for face-to-face teaching a micro-teach activity was developed for student teachers. Micro-teaching is an activity in which student teachers plan, teach and reflect on small lessons, or parts of lessons. This is frequently used in teacher education as an approach to support planning and reflection, yet it typically occurs face-to-face. Reflection is widely recognised as a key skill that student teachers need to develop as part of their teacher education. Video-supported peer reflection was considered appropriate for the student teachers as it offered them opportunities to review and reflect upon their own, as well as others' teaching practice; enabling them to revisit recorded lesson segments as frequently as required. Student teachers were surveyed before and after the micro-teach activity. These survey responses are explored here and include the benefits and challenges of supporting the development of pedagogic skills and peer reflection in an online distance learning environment. Improvements in student teachers' reflection and levels of confidence in peer assessment are also discussed. The most important learning to emerge from the micro-teach activity was the positive impact of the collaborative cross-phase nature of the project, predominantly the reflecting with, and learning from, others.